Pengaruh Gaya Kepemimpinan dan Motivasi Kerja terhadap Kinerja Karyawan pada PT Jaddi Global Indo Jakarta Pusat - Raniyah, Jihan Nur; Lilis Suryani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research aims to determine the influence of work compensation and work motivation on employee performance PT Jaddi Global Indo Central Jakarta. The method used in this research is quantitative method with descriptive approach. The sampling technique is total sampling or census, namely all employees of PT Jaddi Global Indo Central Jakarta, totaling 44 respondents. Data collection through questionnaires or questionnaires. The data analysis methods used are validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, linear regression analysis, coefficient of determination analysis and t test, F test using SPSS Version 25. The results of this study are that leadership style and motivation simultaneously have a positive and significant effect on employee performance with a determination coefficient value of 0.902 x 0.902 = 0.814 or 81.4% and the F hypothesis test obtained Fcount> Ftable or (89.941> 2.83) and a significance value of <0.05 (0.000 <0.05) then H0 is rejected and H3 is accepted, meaning that the variables of leadership style and motivation have a positive and significant effect on employee performance.